Universality at the Edge for Unitary Matrix Models - Poplavskyi, M. (Журнал математической физики, анализа, геометрии, 2012)
Using the results on the 1/n-expansion of the Verblunsky coe±cients for a class of polynomials orthogonal on the unit circle with n varying weight, we prove that the local eigenvalue statistic for unitary matrix models is independent of the form of the potential, determining the matrix model. Our proof is applicable to the case of four times di®erentiable potentials and of supports, consisting of one interval. Используя результат о разложении коэффициентов Верблански для полиномов, ортогональных на единичном круге, с переменным весом по степеням 1-n, доказано, что локальная статистика собственных значений унитарного матричного ансамбля не зависит от вида потенциала, определяющего матричную модель. Доказательство применимо для любого четыре раза дифференцируемого потенциала и носителя, состоящего из одного интервала.